Morphometric Analysis of the Corpus, Spinal Canal and Torg Ratio Using Midsagittal Cervical Vertebrae Computed Tomography Scan: Indonesian Population - Rully Hanafi Dahlan; Priandana Adya Eka Saputra; Farid Farid Yudoyono; Sevline Esthetia Ompusunggu; Muhammad Zafrullah Arifin; Agung Budi Sutiono; Ahmad Faried (Faculty of Medicine Universitas Padjadjaran, 2014)
Objective: To determine the normal ranges of cervical spinal canal morphometry in Indonesian population and to compare the acquired data collected from other populationsMethods: Computed tomography measurements on the diameter of midsagital spinal canal and corpus of cervical vertebrae and its Torg ratio from the lower cervical (C3-C7) canal from 24 normal Indonesian adults were performed at the Radiology Department of Dr. Hasan Sadikin General Hospital. Patients who had cervical spine disorders and those under 20 years old were exluded. We used computed tomography scan midsagittal view to measure the aforementioned parameters. Results: The average diameter for the cervical spinal canals for the Indonesian population is comparable with those of other Asian populations such as Hongkong and India, albeit with smaller Torg ratio. Conclusions: This study reports the normal radiological anatomy of the midsagital spinal canal and corpus of cervical vertebrae as well as Torg ratio from the lower cervical vertebrae among Indonesian population. The measurements result of this study shows that, although slightly smaller, the measurement results for those parameters are identical with other Asian populations. Keywords: Corpus cervical vertebrae, midsagittal cervical spinal canal, Torg ratio DOI: 10.15850/ijihs.v2n1.285